PERANCANGAN DAN IMPLEMENTASI BOT WHATSAPP OTOMATIS MENGGUNAKAN NODE JS DAN BAILEYS BERBASIS WEBSITE (STUDI KASUS: TOKO UNTITLED) - Zalsahra, Rendy; Sujadi, Harun; Suhendri (Universitas Majalengka, 2025)
This study aims to design and implement an automated WhatsApp bot system based on Node.js and the Baileys library, equipped with a web dashboard as a management interface without requiring a Command Line Interface (CLI). The research method follows the Waterfall model, encompassing requirements analysis, system design, implementation, Black-Box testing, and maintenance. Implementation results demonstrate that the WhatsApp bot can automatically respond to customer messages based on keywords, accelerate the sales process of premium digital applications, and improve customer service efficiency at the Untitled store. The web dashboard enables administrators to control the bot and manage message templates more flexibly. The study concludes that the developed system is effective in streamlining digital account sales operations and provides a foundation for further enhancements such as automatic payment integration and the application of Natural Language Processing (NLP).